Atherogenic Burden and Insulin Resistance in Non-Obese Women with Polycystic Ovary Syndrome: A Comparative Study with Healthy Controls - Andaç, Burak; Navdar Başaran, Mehtap; Eren, Gözde Nur (The European Research Journal, 2026)
Objective: Polycystic ovary syndrome (PCOS) is associated with elevated cardiovascular disease (CVD) risk due to metabolic derangements. Although obesity contributes to CVD, the independent contribution of PCOS remains controversial. This study aimed to compare insulin resistance (IR) and atherogenic lipid indices across body mass index (BMI) categories within PCOS, to evaluate the diagnostic performance of atherogenic indices between non-obese PCOS and healthy controls, and to derive exploratory, data-driven thresholds that may inform cardiovascular risk assessment in non-obese PCOS. Methods: This single-center case-control study enrolled 65 treatment-naïve women newly diagnosed with PCOS (Rotterdam criteria 2003) and 100 age-matched healthy controls. A panel of IR and composite atherogenic lipid indices (e.g., Lipid Accumulation Product [LAP], Visceral Adiposity Index [VAI], Triglyceride-Glucose [TyG] Index) was compared between groups. Results: Within PCOS, atherogenic lipid indices were similar in obese versus non-obese subgroups. Non-obese PCOS demonstrated significantly higher atherogenic lipid and IR indices compared to controls (all P